Severity strata for five patient-reported outcomes in adults with atopic dermatitis - Vakharia, P.P. (Br J Dermatol, 2018)
BACKGROUND: Multiple patient-reported outcomes have been used to assess the burden of atopic dermatitis (AD). Some are disease specific, e.g. the Patient Oriented Eczema Measure (POEM). While others pertain to itch, e.g. Numerical Rating Scale (NRS)-itch, ItchyQoL and 5-D itch, or dermatologic disease in general, e.g. Dermatology Life Quality Index (DLQI). Development of severity strata is essential for proper interpretability of these assessments. We sought to confirm previously developed strata for POEM, DLQI and raw ItchyQoL, and develop strata for the NRS-itch, mean ItchyQOL and 5-D itch scale for use in adults with AD. METHODS: Self-administered questionnaires were completed by 210 adults with AD in a dermatology practice setting. Strata were selected using an anchoring approach based on patient-reported disease severity. RESULTS: We confirmed the existing strata for POEM (mild=0–7, moderate=8–16, severe=17–28) (kappa=0.440), DLQI (mild=0–5, moderate=6–10, severe=11–30) (kappa=0.398) and NRS-itch (mild=0–3, moderate=4–6, severe=7–10) (kappa=0.499). However, the preferred band for raw ItchyQoL was mild=22–58, moderate=59–74 and severe=75–110 (kappa=0.379) and mean ItchyQOL was mild=1–2.9, moderate=3.0–3.9, severe=4.0–5.0 (kappa=0.374). The preferred band for 5-D itch scale was mild=0–11, moderate=12–17 and severe=18–25 (kappa=0.331). CONCLUSIONS: Existing strata for POEM and DLQI perform well in adult AD. Previously reported strata for VAS-itch performed best for NRS-itch. We identified banding for the raw ItchyQoL for our AD population that varies slightly from the banding published for a more heterogeneous population. Finally, we proposed strata for mean ItchyQOL and 5-D itch scale in adult AD.